Integrasi Ilmu dan Agama dalam Pendidikan Agama Islam - Chafis, M. Chairul; A. Qomarudin (STAI Ma'had Aly Al-Hikam Malang, 2025)
Islamic Religious Education (PAI) has a strategic role in building a generation that is not only intellectually intelligent, but also has faith and noble morals. One relevant approach is the integration of science and religion, which aims to harmonize spiritual values ​​with scientific progress. This integration is based on the concept of monotheism as a foundation, which confirms that there is no contradiction between Allah's revelation and true science. In the PAI context, this integration can be realized through the study of Al-Qur'an verses that are relevant to scientific phenomena, learning scientific ethics based on Islamic values, and contextual learning approaches. With this approach, students are expected to not only understand Islamic teachings in depth, but also be able to apply them in social life. However, this integration faces various challenges, such as curriculum gaps and limited competency of teaching staff. Therefore, synergy is needed between educational institutions, teaching staff, and educational policies to realize holistic education.